Attitudes Of People In The Thai Construction Industry Sector On Issues Related To Delay In The Approval Of Submittals - Chovichien, Visuth; Suriyanon, Natee (Penerbit Universiti Sains Malaysia, 2011)
This study investigated attitudes in the Thai construction industry sector towards 21 issues related to “delay in the approval of submittals” that may initiate conflicts among various parties. Knowledge gained from this study can be applied to the analyses of the completeness and appropriateness of contract conditions and to improve contract drafting. The attitudes of the majority of people in the industry towards several issues related to the time frame for the approval of submittals, compensation for cost increases and profit losses, and time frames for notifications of delayed approval and claim submission were found to be inconsistent with existing conditions in standard contracts. Various issues that are not covered in the standard contract forms, such as the time frame for providing reminders and the types of time loss and direct costs that can be claimed, were also found to have high tendencies to initiate conflicts between contracting parties. Finally, we also found that the organisational affiliation of the respondents (i.e., employer or contractor) influenced their attitudes towards some, but not all, contractual issues